Follicular growth patterns in repeat breeder cows - C.C. Pérez; I. Rodríguez; F. Espańa; J. Dorado; M. Hidalgo; J. Sanz (Veterinární Medicína, 2003)
The aim of this study was to examine follicular development patterns in eighteen repeat breeder cows through natural oestrus cycles. Ovarian ultrasonographic examinations over 32 days after artificial insemination revealed that two follicular waves were the predominant patterns in animals with this syndrome (72.2%). Cycles with one or four waves rarely appeared. The ovulatory follicular diameter (day 0) was larger (P < 0.01) in cycles with a small number of waves; no differences were detected between ovulatory and anovulatory dominant follicles. Progesterone plasmatic concentrations were determined by RIA and differences were not significant when cycles with two or three waves were compared. The number of follicular waves was higher (2 or 3 waves) with longer interovulatory intervals (22.3 ? 1.89 vs 23.0 ? 2.0; n.s.) and older cows (7.0 ? 2.64 vs. 4.38 ? 1.66 years; P < 0.05). Mean ovulatory follicular diameter was 1.78 ? 0.36 cm. It can be concluded that cows with the RBC syndrome more frequently present two follicular waves, corresponding to longer cycles.